The role of Qualea multiflora on Mammary Tumour Cells and Immune System - Camila B. de A. Carlia, Marcela Bassi Quillesa, Wagner Vilegasb, and Iracilda Z. Carlosa (Journal of Applied Pharmaceutical Science, 2013)
Species of the genus Qualea are used by the Brazilian public as a natural anti-inflammatory. Based on this evidence, we evaluated the effects of terpene fractions (βF and TF) obtained from Qualea multiflora on nitric oxide production (Griess assay), cytokines (IL-1, IL-10, IL-12, and TNF-α) and the transcription factor NF-kB by peritoneal macrophages. Since there is a relationship between inflammation and cancer, the cytotoxicity of βF and TF against mammary tumoural cell lineage, and macrophages was evaluated. Inhibition levels close to 90% of the production of NO, IL-1, IL-12 and TNF-α; about 32% of NF-kB; and a large stimulation of IL-10 production (close to the positive control) by peritoneal macrophages were observed in response to βF and TF which are correlated with anti-inflammatory activity. Additionally, the samples showed exceptional cytotoxic activity against tumoural cells but not against macrophages. Since anti-inflammatory activity is important in tumour inhibition, further examination of potential anti-cancerous activity of Qualea multiflora is warranted.
Keywords: Cancer, Macrophages, Q. multiflora.